2018
DOI: 10.1016/j.ridd.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Stability of bullying and internalizing problems among adolescents with ASD, ID, or typical development

Abstract: During middle adolescence, youth with ASD continue to experience more frequent victimization. Thus, shifting the focus of interventions that not only target the salient social deficits of ASD, but also address comorbid conditions such as internalizing symptoms, may further contribute to reduction of social isolation and peer difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
0
23
1
5
Order By: Relevance
“…The temporal sequence of different levels and types of involvement in bullying and mental health problems warrant longitudinal studies to examine. For example, a longitudinal study revealed that internalizing behaviors at the age of 13 years predicted victimization experiences at the age of 15 years in adolescents with ASD (48). Second, the study participants were adolescents with high-functioning ASD who visited medical units for treatment or survey.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal sequence of different levels and types of involvement in bullying and mental health problems warrant longitudinal studies to examine. For example, a longitudinal study revealed that internalizing behaviors at the age of 13 years predicted victimization experiences at the age of 15 years in adolescents with ASD (48). Second, the study participants were adolescents with high-functioning ASD who visited medical units for treatment or survey.…”
Section: Discussionmentioning
confidence: 99%
“…Above and beyond disability status, higher internalizing behavior problems and peer conflict were significant predictors of victimization. In 2018, Tipton-Fisler and colleagues did a follow-up study with the same youth at age 15 to explore how experiences of bullying and victimization changed for children with TD, ID, and ASD over time [47]. Consistent with Zeedyk et al, [48], they found that adolescents with ASD were bullied more frequently than those with ID or TD.…”
Section: Middle and High Schoolmentioning
confidence: 91%
“…Enduring social difficulties have been found to lead to teasing and bullying by peers, more so for youth with ASD than their typically developing peers [47,48]. Through interviews with early adolescents (age 13) with ASD, Zeedyk and colleagues [48] found that youth with ASD were victimized more frequently than youth with ID or TD.…”
Section: Middle and High Schoolmentioning
confidence: 99%
“…Having a neurodevelopmental disorder has also been studied in relation to child involvement in bullying. Compared to children with typical development for their age, a higher percentage of children with intellectual disability or autism spectrum disorder are involved in bullying [24,25]. Moreover, children with poor executive function [26,27] or with emotional and behavior problems [3,21,[28][29][30][31][32] have also been found to be more likely to be involved in bullying.…”
Section: Introductionmentioning
confidence: 99%